P10.04 Incidence and characteristics of neurological adverse events secondary to immunotherapy with checkpoint inhibitors. (6th September 2019) - Velasco, R; Argyriou, A; Bruna, J; Anastopoulou, G G; Alemany, M; Simó, M; Piulats, J M; Nadal, E; Kalofonos, H P
Abstract: BACKGROUND: To explore the incidence and clinical phenotype of serious neurological adverse events (NAEs) in cancer patients who received immunotherapy with checkpoint inhibitors (ICIs) at two institutions. MATERIAL AND METHODS: We reviewed files of cancer patients who were treated with ICIs from 2010 to 2018 and then searched for ICIs-related NAEs. RESULTS: We identified 1185 ICIs-treated patients. Males and females were 63.7% and 36.3%, respectively, with a mean age of 63.4±7.3 years-old. Nivolumab was given to 536 (45.2%) patients, Pembrolizumab to 301 (25.4%) patients, Atezolizumab to 135 (11.4%), Ipilimumab to 104 (8.8%), Durvalumab-Tremelimumab to 77 (6.5%), and other ICIs to 32 (2.8%). Of those patients, 24 (2%) developed a ICI-related NAE. No differences were identified in age, sex, tumor type and class of ICIs between patients who developed neurotoxicity compared to those without neurologic adverse events. The distribution of NAE by agent was: Nivolumab (2.1%), Pembrolizumab (2%), Atezolizumab (1.5%), Ipilimumab (1%), Durvalumab-Tremelimumab (3.9%), and others (2.8%). The median number of cycles received before NAEs onset were 4.5 (1–10), and the median time was 110 days. PNS involvement was evident in 14 patients (58.3%) and CNS involvement in 41.7%, while 2 patients with aseptic meningitis also presented polyradicular involvement. Among PNS complications, there were 5 cases (20.8%) with axonal sensory neuropathies, 4 (16.7%) with Guillain-Barre-like syndromes, 4 (16.7%) with muscle involvement (myositis and myasthenias), and one with other syndromes. Seven patients (50%) with PNS-related NAEs were treated with steroids, 2 (14.3%) with IVIG, and 5 (35.7%) remained untreated. In general the outcome was good after ICIs discontinuation, with about half of patients improving or completely resolving NAEs. CONCLUSION: ICIs-related NAE although rare overall, might be severe, and are mostly represented by neuromuscular complications. Early discontinuation of ICIs and possibly treatment with immune-modulating therapies should early be initiated to achieve a favourable neurological outcome